The associated risk of Blastocystis infection in cancer: A case control study - Labania, Lena; Zoughbor, Sumaya; Ajab, Suad; Olanda, Marie; Shantour, Sulaiman N. M.; Al Rasbi, Zakeya (Frontiers in Oncology, 2023)
Background Blastocystis is an anaerobic intestinal protozoan. Nine Blastocystis subtypes (STs) were detected in humans. A subtype-dependent association between Blastocystis and different cancer types has been debated in many studies. Thus, this study aims to assess the possible association between Blastocystis infection and cancer, especially colorectal cancer (CRC). We also screened the presence of gut fungi and their association with Blastocystis. Methods We used a case-control design; cancer patients and cancer-free (CF) participants. The cancer group was further sub-group into CRC group and cancers outside the gastrointestinal tract (COGT) group. Macroscopic and microscopic examinations were performed to identify intestinal parasites in participants’ stool samples. Molecular and phylogenetic analyses were conducted to identify and subtype Blastocystis. Furthermore, gut fungi were investigated molecularly. Results 104 stool samples were collected and matched between CF (n=52) and cancer patients (n=52); CRC (n=15) and COGT (n=37). As anticipated, Blastocystis prevalence was significantly higher among CRC patients (60%, P=0.002) and insignificant in COGT patients (32.4%, P=0.161) compared to CF group (17.3%). The most common subtypes were ST2 among cancer group and ST3 in the CF group. Conclusion Cancer patients have a higher risk of Blastocystis infection compared to CF individuals (OR=2.98, P=0.022). Increased risk of Blastocystis infection was associated with CRC patients (OR=5.66, P=0.009). Nevertheless, further studies are required to understand the underlying mechanisms of Blastocystis and cancer association.